2018
DOI: 10.1126/scisignal.aao1716
|View full text |Cite
|
Sign up to set email alerts
|

The pseudokinase MLKL activates PAD4-dependent NET formation in necroptotic neutrophils

Abstract: Neutrophil extracellular trap (NET) formation can generate short-term, functional anucleate cytoplasts and trigger loss of cell viability. We demonstrated that the necroptotic cell death effector mixed lineage kinase domain-like (MLKL) translocated from the cytoplasm to the plasma membrane and stimulated downstream NADPH oxidase-independent ROS production, loss of cytoplasmic granules, breakdown of the nuclear membrane, chromatin decondensation, histone hypercitrullination, and extrusion of bacteriostatic NETs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 71 publications
1
89
0
1
Order By: Relevance
“…Prior study indicated that the necroptotic cell death effector MLKL phosphorylation forming a polymer which translocated from the cytoplasm to the plasma membrane to perforation (45)(46)(47)(48). Prior study indicated that MLKL phosphorylation could stimulate downstream NADPH oxidase-independent ROS production, breakdown of the nuclear membrane, and induce NETs formation (49). So we speculate that Nec-1 suppresses the release of NETs by inhibiting phosphorylation and perforation of MLKL.…”
Section: Discussionmentioning
confidence: 74%
“…Prior study indicated that the necroptotic cell death effector MLKL phosphorylation forming a polymer which translocated from the cytoplasm to the plasma membrane to perforation (45)(46)(47)(48). Prior study indicated that MLKL phosphorylation could stimulate downstream NADPH oxidase-independent ROS production, breakdown of the nuclear membrane, and induce NETs formation (49). So we speculate that Nec-1 suppresses the release of NETs by inhibiting phosphorylation and perforation of MLKL.…”
Section: Discussionmentioning
confidence: 74%
“…Another pore-forming protein MLKL (not related to gasdermins) is activated by RIP kinases during necroptosis. Activation of MLKL in neutrophils can also lead to the release of NETs [ 11 - 13 ].…”
Section: Mechanisms Of Netosismentioning
confidence: 99%
“…The signaling mechanisms of NETosis may include activation of phosphoinositide-3-kinase (PI3K) [ 9 ], which also controls the autophagy induction, but assembly of autophagosomes is not required for NETosis [ 10 ]. The pathways leading to NETosis and necroptosis can be especially closely intertwined [ 11 - 13 ]. For a long time, it was believed that mitochondria do not play a significant role in the functioning of neutrophils, since their content in these cells is low, energy supply is supported by glycolysis, and NADPH oxidase is the main source of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the observation that death effector proteins drive NET expulsion, a recent study likewise reported that MLKL, the death effector in the necroptosis pathway, promotes NETosis in necroptotic neutrophils. Mechanistically, MLKL‐driven plasma membrane pores promote calcium influx, PAD4 activation, and NET release 112 . Importantly, Pad4‐ deficient neutrophils fail to undergo NETosis in necroptotic neutrophils, while PAD4 is dispensable for non‐canonical NETosis.…”
Section: Programmed Cell Death During Bacterial Infectionmentioning
confidence: 99%